A comparison of demographic profiles, clinical profile, course, and outcome of Bipolar I Disorder and Bipolar II Disorder: Findings from the Bipolar Disorder Course and Outcome study from India (BiD-CoIN study) - Grover, Sandeep; Avasthi, Ajit; Chakravarty, Rahul; Dan, Amitava; Chakraborty, Kaustav; Neogi, Rajarishi; Desouza, Avinash; Nayak, Omkar; Praharaj, Samir Kumar; Menon, Vikas; Deep, Raman; Bathla, Manish; et al. (Indian journal of psychiatry, 2024)
Background: There is lack of data on bipolar disorder (BD) type II from India. Aim: To compare the demographic and clinical characteristics of patients with BD-I and BD-II using the data of the Bipolar Disorder Course and Outcome study from India (BiD-CoIN study). Methodology: Using the data of the BiD-CoIN study, patients with BD-I and BD-II were compared for demographic and clinical variables. Results: Out of the 773 patients, 59 (7.63%) participants had BD-II. Compared to BD-I, patients with BD-II had a higher income; were more often unemployed or housewives; had a higher mean number of episodes per year of illness, higher severity of depressive episodes, higher depressive affective morbidity, and a higher number of hypomanic episodes (in the lifetime, and number of episodes per year of illness); received lower doses of lithium and a lower number of medications; and had lower prevalence of alcohol dependence, higher prevalence of seasonality, a high proportion of them sought faith healing treatment, and a higher proportion of them have predominant depressive polarity. Conclusions: Patients with BD-I and BD-II differ from each other on certain demographic and clinical variables. The difference in the clinical variables suggests that the patients with BD-II may require different treatment approaches for management.